Global experience of antimicrobial stewardship integration in electronic medical records: a scoping review - Mahmud, Aidalina; Ahmed Talal, Bany Hamdan Abdullah; Abdul Manaf, Rosliza; Alawdah, Laila (Malaysian Public Health Physicians Association, 2024)
Antimicrobialresistance impedesthe efficacy of currently available antimicrobial drugs for treatinginfectious diseases.Antimicrobial stewardship (AMS) practices contributetoin haltingantimicrobial resistance by ensuring appropriate antimicrobial prescription. Consequently, many hospitals nowadaysutilize electronic medical records(EMR) as a platform to enhanceAMS practices among their healthcare professionals. The impact of EMR-based AMS modules needsto be ascertained.This scoping review aims to describe the impact of AMSPrograms implemented through EMRon a global scale.A scoping review was conducted using the methodological framework of Arksey and O’Malley, in addition to the Joanna Briggs Institute. A comprehensive search was conducted on PubMed and Google Scholar databases for literature published between 2014 and 2021 using the keywords "antimicrobial", "stewardship", and "electronic medical records". Two reviewers independently screened the titles and abstracts of articles based on the "Population-Concept-Context" framework, using predefined inclusion and exclusion criteria.Atotal of 20studies were included. Most of these studies were conducted in the United States (n=12) and the remaining studies were conducted in various countries,including the United Kingdom, Australia, Indonesia, Egypt, Canada, the Netherlands, Saudi Arabia, and South Korea. The studies demonstrated the global impact of integrating the AMS program in the EMR. The review declaresthat EMR adoption can provide healthcare providerswith efficient processes given the availabilityof clinical data that guide appropriateantimicrobial use. Additionally, implementinginformation technologies for AMS facilitates adherence tonational and international clinical practice guidelines and standardizesantimicrobial usage for optimal patient care.